Research, analysis, and assessment of the Bulgarian population’s preparedness to provide first aid (International Journal of Scientific Research and Management (IJSRM), 2021)
In Bulgaria, there are no statistics on the attitude of the society to the topic of first aid and the extent and scale of the trained people. This fact gave rise to the need to prepare and conduct a study, the results of which will illustrate more about the topic. The aim of this study is to understand more on whether people are ready to provide first aid and what makes them feel confident/insecure to help in case of an accident or acute illness. The methods used are developing and testing a questionnaire, collecting qualitative and quantitative data through an online survey and evaluation, analysis, and interpretation of the collected data. The results show, that a very small part of the respondents has sustainable knowledge and skills in first aid, which leads to a reduced readiness to help the casualty. This is rooted not in the unwillingness to help, but in the low confidence in the training received. The lack of regular repetitive training increases people’s feelings of insecurity, prevents them from acting when needed, leading to a number of large-scale complications such as increasing the burden on health care, in the form of additional costs for subsequent hospital stays/treatment. The data collected from the study will be used to develop suggestions for the implementation of innovative training programs to fill the gaps in preparing the population for first aid, and subsequently on the social and health well-being of society by increasing survival rate and respectively saving lives.